2016
DOI: 10.1002/bkcs.10861
|View full text |Cite
|
Sign up to set email alerts
|

Preformulation of FK506 Prodrugs for Improving Solubility

Abstract: In order to improve water solubility of a lipophilic drug, tacrolimus (FK506), two prodrugs (FK506-G or FK506-S) such as FK506-M32-LS-G (FK506-G) and FK506-M32-LS-SL (FK506-S) were synthesized. Two prodrugs (FK506-G or FK506-S), including FK506, were characterized by differential scanning calorimetry (DSC), X-ray diffractometry (XRD), scanning electron microscopy (SEM), enzymatic kinetics, and cytotoxicity. A phase solubility test was conducted in distilled water, and the solubility of two prodrugs (FK506-G or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…The whole blood stability of the HA-ss-TAC conjugate was assessed in rat blood using a previously reported protocol. , Fresh whole blood was obtained from control Wistar rats in our institutional animal house. A stock solution of HA-ss-TAC conjugate was prepared in a solvent mixture of DMSO and water: (20:80, % v/v).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The whole blood stability of the HA-ss-TAC conjugate was assessed in rat blood using a previously reported protocol. , Fresh whole blood was obtained from control Wistar rats in our institutional animal house. A stock solution of HA-ss-TAC conjugate was prepared in a solvent mixture of DMSO and water: (20:80, % v/v).…”
Section: Methodsmentioning
confidence: 99%
“…In the past decade, several alternative formulations such as self-microemulsifying drug delivery systems (SMEDDS), hydrogels, , liposomes, ethosomes, inclusion complexes, solid dispersions, micelles, , and nanoparticles have been utilized for improvement of TAC solubility. Along with this, many water-soluble prodrugs of TAC were synthesized with polymers such as polyethylene glycol (PEG), cyclodextrin, glucose, or sialic acid using a succinyl linker. These prodrugs are often transformed into parent TAC through the hydrolysis of ester linkage by the esterase enzyme present in plasma and various tissues.…”
Section: Introductionmentioning
confidence: 99%
“…FK506 (tacrolimus, Figure 1Dii ) is an FDA-approved immunosuppressive drug originally produced by Streptomyces tsukubensis . It is currently used in the treatment of patients undergoing organ transplants, but also displays the potential to be used as an antifungal, neuroprotective and neuroregenerative agent ( Jung et al, 2021 ), and as therapy for conjunctivitis ( Na et al, 2016 ). However, in order to broaden its use to neuronal diseases, conjunctivitis and as an antifungal, its immunosuppressive activity must be abolished and its water solubility improved.…”
Section: Immunosuppressive Compoundsmentioning
confidence: 99%
“…The same process could be applied to obtain the corresponding C-42 PEG-analog of rapamycin ( González-Sabín et al, 2011 ). The structure of the abovementioned derivatives was confirmed using ESI-MS. Na et al have also reported obtaining two water-soluble conjugates of FK506 via a spontaneous reaction of FK506 with a succinyl linker followed by an enzymatically catalyzed conjugation of glucose (affording FK506-G, Supplementary Table S1 , row xii) or amino carbohydrate sialic acid (FK506-S, Supplementary Table S1 , row xiii) by glucosyltransferase or sialyltransferase, respectively, and these conjugates were quantified by HPLC analysis ( Na et al, 2016 ).…”
Section: Immunosuppressive Compoundsmentioning
confidence: 99%
“…Kekambuhan pada satu tahun terdiagnosa skizofrenia dialami oleh 60-70% pasien yang tidak mendapatkan pengobatan, 40% pasien hanya mendapat pengobatan, 15,7% pada pasien yang mendapat kombinasi terapi pengobatan dan mendapat dukungan dari tenaga kesehatan, keluarga dan masyarakat (Stuart, 2007). Prevalensi kekambuhan pada pasien skizofrenia itu sendiri berada dalam rentang 50-92% secara global (Waret and Mukherjee, 2014).…”
Section: Pendahuluanunclassified